Multitasking Student Workers: The Role of Part-time job and Time Management in Learning Activities - Priyanto, Priyanto; Hastuti, Farida Tri; Wardani, Galuh Kusuma; Paksi, Angger Binuko (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates the impact of part-time jobs on students' learning activities, with time management as a mediating factor. Using a quantitative approach and SmartPLS 4, data were collected from 74 students at the State Polytechnic of Madiun. Results show that part-time jobs do not directly affect learning activities (t = 1.890, p = 0.059). However, they significantly influence time management (t = 6.463, p = 0.000), which in turn positively affects learning activities (t = 6.945, p = 0.000). The R² values indicate that 34% of learning activities and 28.5% of time management are explained by the proposed model.